Performa Rapid Diagnostik Tes Hepatitis B dengan ELISA sebagai Gold Standar - I Gusti Ayu Sri Andayani; Mohammad Rizki; Made Sriasih; Ika Nurfitria Tauhida (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
The ELISA (Enzyme Linked Immunoassay) method has high sensitivity and specificity, qualitatively and quantitatively detecting Hepatitis B Surface Antigen (HBsAg) levels, but the process is long, expensive and requires special expertise, compared to the Rapid Diagnostic Test (RDT) as a rapid test which is more practical and cheaper. The aim of this study was to compare the sensitivity and specificity of the Entebe Rapid Test Diagnostic (ERTD) produced by PT. Hepatika Mataram, with ELISA as the gold standard in detecting HBsAg. The requirement for interpreting sensitivity and specificity results according to World Health Organization (WHO) standards is a minimum of 95%. Testing with a negative panel of 00 samples and a positive panel of 1 samples from Papua in 012 at -80℃ storage. Testing in April 023 at the Molecular Diagnostics and Research Laboratory, Mataram University Hospital. Statistical analysis using MedCal software. ERD HBsAg produced by PT. Hepatika Mataram has a sensitivity of 95.45%, specificity of 99.50%, positive predictive value of 93.59%, negative predictive value of 99.65%, and accuracy of 99.21%.